Linking stomatal traits and expression of slow anion channel genes HvSLAH1 and HvSLAC1 with grain yield for increasing salinity tolerance in barley - Liu, Xiaohui; Mak, Michelle; Babla, Mohammad; Wang, Feifei; Chen, Guang; Veljanoski, Filip; Wang, Gang; Shabala, Sergey; Zhou, Meixue; Chen, Zhong-Hua (Frontiers in Plant Science, 2014)
Soil salinity is an environmental and agricultural problem in many parts of the world. One of the keys to breeding barley for adaptation to salinity lies in a better understanding of the genetic control of stomatal regulation. We have employed a range of physiological and molecular techniques (stomata assay, gas exchange, phylogenetic analysis, QTL analysis, and gene expression) to investigate stomatal behaviour and genotypic variation in barley cultivars and a genetic population in four experimental trials. A set of relatively efficient and reliable methods were developed for the characterisation of stomatal behaviour of large numbers of varieties and genetic lines. Furthermore, we have found a large genetic variation of gas exchange and stomatal traits in barley in response to salinity stress. Salt-tolerant CM72 showed significantly larger stomatal aperture in 200 mM NaCl treatment than that of salt-sensitive Gairdner. Stomatal traits such as aperture width/length were found to significantly correlate with grain yield in salt treatment. Phenotypic characterisation and QTL analysis of a segregating double haploid population of the CM72/Gairdner resulted in the identification of significant stomatal traits-related QTLs for salt tolerance. Moreover, expression analysis of the slow anion channel genes HvSLAH1 and HvSLAC1 demonstrated that their up-regulation is linked to high barley grain yield in the field.